Asthma Mortality Inequalities in Brazil: Tolerating the Unbearable - Carolina de Souza-Machado; Adelmir Souza-Machado; Alvaro A. Cruz (The Scientific World Journal, 2012)
Asthma is responsible for a high morbidity, resulting in hospitalizations, recurrent asphyxiation, and eventually death. In Brazil, where asthma is the third cause of hospitalizations for clinical illnesses and the fourth cause of death from respiratory diseases, some 20% of the population present wheezing. We evaluated the asthma mortality rates in the period between 1998 and 2009, using linear regressions, using the National Mortality Database (Ministry of Health of Brazil). The annual mortality rate (per 100,000 inhabitants) ranged from 1.68 in 1998 to 1.32 in 2009 (mean : 1.49). Brazil presents a slight tendency of reduction in asthma mortality. Asthma mortality rates trends declined in the most developed regions of the country:  Midwest, South, and Southeast, but it increased in the underprivileged regions: North (not statistically significant) and Northeast. This terrible sort of inequality requires urgent reaction from the public health authorities.